Cutting EDGE. Upper Intermediate: Students' Book with mini-dictionary - Cunningham S. Sarah (Harlow, Longman, 2005)
Cutting Edge is a multi-level general English course for adults and young adults. It combines rich international content, comprehensive grammar, and real-life functional language within a clear, easy-to-teach structure. Cutting Edge includes these additional key features: High-frequency, useful vocabulary A special focus on phrases and language 'chunks' makes vocabulary easy to remember and easy to use Regular, well-structured speaking tasksA straightforward structure of task preparation, performance and outcome develops students' speaking skills Complete teaching programme Unique Mini-dictionary helps train the learner to study independently Teacher's Resource Books with a large bank of photocopiable activities, teacher's tips and alternative teaching suggestions Videos and Video Workbooks with varied documentary-style features Companion Website with extra resources, web links and chat facilities